Novel nostalgias : the aesthetics of antagonism in nineteenth-century U.S. literature - Funchion, John (The Ohio State University Press, 2015)
"Novel Nostalgias: The Aesthetics of Antagonism in Nineteenth-Century U.S. Literature establishes how the longing to recover a lost home or past drove some of the central conflicts of the nineteenth-century United States. Providing one of the few U.S. literary histories that examines cultural material from both before and after the Civil War, John Funchion argues that a diverse array of novels, from William Wells Brown's Clotel to L. Frank Baum's The Wonderful Wizard of Oz, imagined new politically--and antagonistically--charged communities through forms of nostalgic longing."